2006
DOI: 10.1016/j.orggeochem.2006.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of carbohydrates through sulfurization in a Jurassic euxinic shelf sea: Examination of the Blackstone Band TOC cycle in the Kimmeridge Clay Formation, UK

Abstract: A complete total organic carbon (TOC) cycle in the Upper Jurassic Kimmeridge Clay Formation (KCF) comprising the extremely TOC-rich (34%) Blackstone Band was studied to investigate the controlling factors on TOC accumulation. Compared with the under-and overlying strata, TOC in the Blackstone Band was enriched by a factor of six and, concomitantly, the d 13 C TOC shows a $4& enrichment. Al-normalized TOC values indicated that the enhanced TOC values were probably caused by increased TOC accumulation and not by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 76 publications
4
33
1
Order By: Relevance
“…10c). This is consistent with the idea that the C 28 28,30-dinorhopene IV and, thus, its diagenetic derivatives V-VII, can be used as stratification markers since it is well established that the Blackstone Band was deposited in a stratified, euxinic shelf sea (van KaamPeters et al, 1997KaamPeters et al, , 1998van Dongen et al, 2006a) as is also evident from increased levels of isorenieratene derivatives (Fig. 10b).…”
Section: Aromatisation Of C 28 2830-dinorhop-13(18)-enesupporting
confidence: 86%
See 2 more Smart Citations
“…10c). This is consistent with the idea that the C 28 28,30-dinorhopene IV and, thus, its diagenetic derivatives V-VII, can be used as stratification markers since it is well established that the Blackstone Band was deposited in a stratified, euxinic shelf sea (van KaamPeters et al, 1997KaamPeters et al, , 1998van Dongen et al, 2006a) as is also evident from increased levels of isorenieratene derivatives (Fig. 10b).…”
Section: Aromatisation Of C 28 2830-dinorhop-13(18)-enesupporting
confidence: 86%
“…The C 24 tetra-aromatic and C 25 triaromatic members of this series were identified in relatively high concentrations in the Messel oil shale (Greiner et al, 1976(Greiner et al, , 1977 and have subsequently been found, together with the C 26 diaromatic and C 27 monoaromatic members (V-VI), in many other, often thermally immature, organic matter-rich sediments (e.g., Barnes et al, 1979;Comet et al, 1981;Simoneit, 1981;Rullkötter et al, 1984;van Kaam Peters et al, 1997;van Dongen et al, 2006a). Their structures suggest a diagenetic sequence of successive aromatization reactions from ring D through rings C, B, and A (Greiner et al, 1976(Greiner et al, , 1997 (Fig.…”
Section: Aromatisation Of C 28 2830-dinorhop-13(18)-enementioning
confidence: 99%
See 1 more Smart Citation
“…Li et al (2011) found elevated concentrations of organic sulfur in suspended particles near the chemocline in the Cariaco Basin water column and proposed that this indicated early OM sulfurization. Rapid OM sulfurization in particles sinking through the water column was also proposed to explain the high S:C ratios in certain OM-rich rocks (van Dongen et al, 2006;Tribovillard et al, 2004). Support for the feasibility of more rapid OM sulfurization is also provided by laboratory experiments.…”
Section: Introductionmentioning
confidence: 91%
“…6) in bulk organic matter from the Kimmeridge Clay Formation (KCF) of southern England (Morgans-Bell et al 2001). However, the enhanced δ 13 C TOC values in the KCF mostly correlate with enhanced TOC values that probably result from enhanced preservation of carbohydrates through sulphurization (van Dongen, Schouten & Sinninghe Damste, 2006). They are most likely caused by a longer duration of photic zone euxinia in the depositional environment and do not reflect the overall composition of dissolved inorganic carbon in seawater.…”
Section: A General Carbon-and Oxygen-isotopic Trends In the Kimmermentioning
confidence: 99%